Expression and Characterization of Relaxin Family Peptide Receptor 1 Variants - Speck, David; Kleinau, Gunnar; Meininghaus, Mark; Erbe, Antje; Einfeldt, Alexandra; Szczepek, Michal; Scheerer, Patrick; Pütter, Vera (Frontiers in Pharmacology, 2022)
G-protein coupled receptors (GPCR) transduce extracellular stimuli into the cell interior and are thus centrally involved in almost all physiological-neuronal processes. This essential function and association with many diseases or pathological conditions explain why GPCRs are one of the priority targets in medical and pharmacological research, including structure determination. Despite enormous experimental efforts over the last decade, both the expression and purification of these membrane proteins remain elusive. This is attributable to specificities of each GPCR subtype and the finding of necessary experimental in vitro conditions, such as expression in heterologous cell systems or with accessory proteins. One of these specific GPCRs is the leucine-rich repeat domain (LRRD) containing GPCR 7 (LGR7), also termed relaxin family peptide receptor 1 (RXFP1). This receptor is characterized by a large extracellular region of around 400 amino acids constituted by several domains, a rare feature among rhodopsin-like (class A) GPCRs. In the present study, we describe the expression and purification of RXFP1, including the design of various constructs suitable for functional/biophysical studies and structure determination. Based on available sequence information, homology models, and modern biochemical and genetic tools, several receptor variations with different purification tags and fusion proteins were prepared and expressed in Sf9 cells (small-scale), followed by an analytic fluorescence-detection size-exclusion chromatography (F-SEC) to evaluate the constructs. The most promising candidates were expressed and purified on a large-scale, accompanied by ligand binding studies using surface plasmon resonance spectroscopy (SPR) and by determination of signaling capacities. The results may support extended studies on RXFP1 receptor constructs serving as targets for small molecule ligand screening or structural elucidation by protein X-ray crystallography or cryo-electron microscopy.